Photograph of girls petting dogs and a descriptive note - United States. Army. Signal Corps (photographer):::Creator::::::::::::
This item contains a photograph showing a group of girls petting two pugs that are pets kept in special kennels by members of the Fort Ord WAC detachment and a typewritten note describing the photograph.